The re-discovery of Arma dell'Aquila (Finale Ligure, Italy): New insights on Neolithic funerary behavior from the sixth millennium BCE in the north-western Mediterranean. (10th April 2019) - Sparacello, V.S.; Panelli, C.; Rossi, S.; Dori, I.; Varalli, A.; Goude, G.; Starnini, E.; Biagi, P.
Abstract: Evidence of Neolithic occupation at Arma dell'Aquila (Finale Ligure, Italy) had been unearthed in the 1930s, with the discovery of nine burials and a number of scattered human remains. The material, however, had never been systematically studied and characterized chronologically until recently. We performed a complete re-assessment of funerary behavior at the site, and studied for the first time the scattered human remains, cross-referencing the anthropological data with the spatial and stratigraphic information contained in the original excavation diaries, and with new direct radiocarbon dates on human bone. Results reveal the funerary use of the site throughout the sixth millennium BCE, when various cultural horizons belonging to the Impresso-Cardial cultural complex have succeeded one another, and during the fifth millennium BCE, when the Square Mouthed Culture was attested in Liguria. Five burials spanning the second half of the sixth millennium BCE were aligned head-against-head and feet-against-feet, crouched on their left side, and may be part of an organized funerary space used over a relatively long period of time. Among the nine individuals recognized from the scattered human remains, three date to c. 5750-5650 BCE, and represent the oldest human remains from a Neolithic context in the north-western Mediterranean. Arma dell'Aquila now constitutes an important source of information on the funerary behavior and biological makeup of Neolithic people of the sixth millennium BCE, a period for which little information was previously present in the region.